Search for production of single top quarks via tcg and tug flavor-changing-neutral-current couplings - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We search for the production of single top quarks via flavor-changing- neutral-current couplings of a gluon to the top quark and a charm (c) or up (u) quark. We analyze 230pb-1 of lepton+jets data from pp̄ collisions at a center of mass energy of 1.96 TeV collected by the D0 detector at the Fermilab Tevatron Collider. We observe no significant deviation from standard model predictions, and hence set upper limits on the anomalous coupling parameters κgc/Λ and κgu/Λ, where κg define the strength of tcg and tug couplings, and Λ defines the scale of new physics. The limits at 95% C.L. are κgc/Λ<0.15TeV-1 and κgu/ Λ<0.037TeV-1. © 2007 The American Physical Society.